PENGARUH SOCIAL MEDIA INSTAGRAM TERHADAP KEPUTUSAN PEMBELIAN, MELALUI BRAND AWARENESS - Handono, Artiar Anjani; Madiawati, Putu Nina (JURISMA : Jurnal Riset Bisnis & Manajemen, 2021)
Tridaya is one of the tutoring service institutions in the city of Cirebon. In the last 3 periods, there has been a decrease in the number of students from each period. The very rapid development of social media is currently being used by Tridaya as a medium to communicate its products. So that the purpose of this study is that the researcher wants to know the magnitude of the influence of social media through Instagram on purchasing decisions through brand awareness as an intervening variable. The data analysis method used in this study is Structural Equation Modeling (SEM) with the use of a data processing application, namely SmartPLS. The results of descriptive research regarding respondents' responses to social media variables, brand awareness variables, and purchasing decision variables are in a good category. To test the hypothesis by looking at the t-statistic value, it shows that all the proposed hypotheses are accepted, so it can be concluded that in this study social media through Instagram @ Tridaya. Cirebon has a positive and significant effect on purchasing decisions with brand awareness as an intervening medium.